Evidence that an unnamed isometric virus associated with potato rugose disease in Peru is a new species of torradovirus - Álvarez, R.A.; Amao, M.; Muller, G.; Fuentes, S.; Grinstead, S.; Fuentes-Bueno, I.; Roenhorst, A.; Westenberg, M.; Botermans, M.; Kreuze, Jan F.; Mollov, D. (Scientific Societies, 2023)
A previously uncharacterized torradovirus species infecting potatoes was detected by high-throughput sequencing from field samples from Peru and in customs intercepts in potato tubers originated from South America in the USA and the Netherlands. This new potato torradovirus showed high nucleotide sequence identity to an unidentified isometric virus(SB26/29), which was associated with a disease named potato rugose stunting in southern Peru characterized over two decades ago. Thus, this virus is tentatively named potato rugose stunting virus (PotRSV). The genome of PotRSV isolates sequenced in this study were composed of two polyadenylated RNA segments. RNA1 ranges between 7,086-7,089 nt and RNA2 from 5,228 to 5230 nt. RNA1 encodes a polyprotein containing the replication block (Helicase-Protease-Polymerase), whereas RNA2 encodes a polyprotein cleaved into a movement protein and the three capsid proteins (CPs). Pairwise comparison among PotRSV isolates revealed amino acid identity values >86% in the protease-polymerase (Pro-Pol) region and >82% for the combined CPs. The closest torradovirus species, squash chlorotic leaf spot virus, shares amino acid identities of ~58% and ~41% in the Pro-Pol and the combined CPs, respectively.